The development of Islamic feminism in Malaysia - Indriaty Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper is produced with the aim of examining the traces of feminist thinking that is rooted in Malaysia. Feminism is a movement that fights for women’s human rights from discrimination by all parties whether men, communities, or authorities until they achieve the desired emancipation and justice. Its historical background is traced among women as early as its growth after independence in 1957 until its latest development in the 2020s. The methodology used in the production of this writing is entirely armchair research. Data were mostly obtained from individual workbooks, seminar papers, research results, newspaper clippings and online data. The study found that the development of feminism in Malaysia can be categorized according to its growth period, namely after independence in the 1960s, 1970-1980s and finally, the 1990s until present. In each category of those years, feminism presented ideologies and demands in accordance with the developments of its time. This has shaped the uniqueness of Malaysian-style feminism born out of local needs and demands and should continue to evolve in a way that does not conflict with the Malaysian Islamic views and culture.